Effect of intermittent fasting diet on triglyceride levels in Sprague Dawley rats - Esa Indah Ayudia; Andini Agustina; Huntari Harahap; Miftahurrahmah Miftahurrahmah; Irfannuddin Irfannuddin (JURNAL KEDOKTERAN DAN KESEHATAN, 2021)
Triglycerides are the main lipid components that are stored in adipose tissue for energy sources. Increased triglyceride levels can lead to cardiovascular disease. One way to lower triglyceride levels is diet. The intermittent fasting diet is one of the diets that can be done, where this diet is a diet with time and calorie restrictions. The intermittent fasting diet is divided into 3 methods, namely Time restricted feeding, Alternate-day fasting and Modified fasting. This study was conducted to see the effect of an intermittent fasting diet on triglyceride levels. This research is an experimental study using white rats of Sprague Dawley strain as experimental. White rats will be divided into 3 groups of intermittent fasting diet and 1 control group and given a diet according to the group for 1 month. Weights and blood draws were performed at the beginning and end of the study, then the results of the intermittent fasting diet intervention were compared with the control group. There was a significant reduction in body weight with a p value of 0.000 and a significant decrease in triglyceride levels with a p value of 0.035 (p <0.05). Keywords : Triglycerides, Intermittent Fasting Diet, Weight loss.